Authority, ascendancy, and supremacy : China, Russian, and the United States' pursuit of relevancy and power - Hall, Gregory Otha (Abingdon, Oxon : Routledge, 2014)
"Authority, Ascendancy, and Supremacy examines the American, Chinese, and Russian (Big 3) competition for power and influence in the Post-Cold War Era. With the ascension of regional powers such as India, Iran, Brazil, and Turkey, the Big 3 dynamic is an evolving one, which cannot be ignored because of its effect to not only reshape regional security, but also control influence and power in world affairs
1. The tripolar conflict, cooperation, and competition (TC) order -- 2. International theories and concept: why authority, ascendancy, and supremacy works -- 3. The cold war bipolar international system and the evolution of the strategic triangle -- 4. The role and function of authority, ascendancy, and supremacy on the contemporary world stage -- 5. The China factor in the triangle politics of the post-cold war period -- 6. The Russia factor in the triangular politics of the post-cold war period -- 7. The United States and the triangular politics of the post-cold war period -- 8. Who's in the triangle? important actors and issues for the big3 powers -- 9. Conclusion: whither the politics of the strategic triangle?
Includes bibliographical references (p. [165]-177) and index
Keywords: Hegemony; International cooperation; World politics -- 1989-